Kinship and consumption: the effect of spouses' outside options on household productivity - Telalagic, S (University of Oxford, 2014)
This paper provides a causal reason for failure in productive efficiency in the household and explains why some households may be less efficient than others. In the theoretical model, spouses make labour allocation decisions in each period to generate income, facing a threat of divorce in the next period. This threat of divorce encourages spouses to invest in their outside options. If decision-making is noncooperative, asymmetric outside options lead to lower productivity. Using exogenous variation in inheritance rules in Malawi as a measure of outside options, the empirical results show that matrilineal households (where women have access to land) have 10% higher consumption than patrilineal households (where women have no access to land). These resuls are robust to a wide variety of specifications and are corroborated by an analysis of labour allocation and income. The results suggest that variation in spouses' outside options can help explain variation in household productivity.